Management of Tuberculosis in Taiwan:A Look into the Shared Responsibilities of the Government, General Public and Medical Students - Chia Liu; Yuh-Jue Chen; Edward Chen; Scott Yi-Heng Lin (Journal of Asian Medical Students' Association, 2026)
Tuberculosis (TB) is a deadly infectious disease worldwide due to its high incidenceand mortality rate. Its impact on Taiwan is no exception. This paper aims to examineeffectiveness of national policies on TB control, assess public awareness, and evaluatewhether involvement of medical students would have a positive effect towards TBcontrol in Taiwan.Literatures were first reviewed to assess effectiveness of Directly Observed Treatment,Short-course (DOTS). Although there is limited improvement in treatment success inTaiwan, there is an overall positive effect.Questionnaires designed to assess public knowledge and behaviors revealedinadequate public knowledge about DOTS, which could have led to the lack ofdistinct success in the national policy. Healthcare workshops were conducted by medical students, with survey resultsshowing a significant improvement in participants’ knowledge. Thus, medicalstudents are recommended to engage in healthcare activities to effectively aid TBcontrol.